Chemical health risk assessment at the thermodynamic laboratory, University of Malaya / Goh Zhi Kee - Goh, Zhi Kee (2021)
Use of chemicals in university laboratory is unavoidable as it is part of the teaching and learning process. Chemical exposure could lead to acute or chronic occupational diseases and even leads to fatality if the chemical is not handled properly. Therefore, chemical health risk assessment (CHRA) plays an important role to evaluate the risk of chemical hazardous to health used at the Thermodynamic Laboratory, University of Malaya, by referring to the Manual of Recommended Practice on the Assessment of the Health Risks Arising from the Use of Chemicals Hazardous to Health at the Workplace 3rd Edition. The assessment was divided into 3 main phases, which are data collection, on-site assessment, and risk evaluation. Action priority was assigned for each chemical assessed to establish the action plan if further control measures needed. Methanol is required for the highest priority as it has the highest risk rating for both inhalation and dermal, followed by benzoic acid, boric acid, diethanolamine, ethanolamine, silver oxide and sulfuric acid as these chemicals resulted high risk for dermal exposure. The management shall consider to give the access permission to handle these chemicals only to the authorized personnel. This study is beneficial to the university management in order to comply to the Occupational Safety and Health (Use and Standards of Exposure of Chemicals Hazardous to Health) Regulations 2000 as chemical health risk assessment is mandatory to be conducted at workplace in every 5 years.